2020
DOI: 10.1128/aem.02291-19
|View full text |Cite
|
Sign up to set email alerts
|

CmAim24 Is Essential for Mitochondrial Morphology, Conidiogenesis, and Mycoparasitism in Coniothyrium minitans

Abstract: Coniothyrium minitans is an important mycoparasite of the notorious phytopathogenic fungus Sclerotinia sclerotiorum. The mycoparasitism system of C. minitans-S. sclerotiorum is unique and important in probing fungi and fungal interactions. Here, we report a conidiation-deficient mutant, ZS-1TN1961, which was screened from a transfer DNA (T-DNA) insertional library of C. minitans. A single-copy gene, encoding a protein with high sequence similarity to Aim24 (altered inheritance of mitochondria protein 24) in Sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
(41 reference statements)
0
4
0
Order By: Relevance
“…Similar to S. cerevisiae, MoAlo1 is located in the mitochondria (Figure 1C), suggesting that MoAlo1 may function as ScAlo1. Disruption of some mitochondrial proteins showed significant conidiogenesis and germination defects [32], consistent with ∆Moalo1. Mitochondria are some of the most important organelles of cells.…”
Section: Discussionmentioning
confidence: 57%
“…Similar to S. cerevisiae, MoAlo1 is located in the mitochondria (Figure 1C), suggesting that MoAlo1 may function as ScAlo1. Disruption of some mitochondrial proteins showed significant conidiogenesis and germination defects [32], consistent with ∆Moalo1. Mitochondria are some of the most important organelles of cells.…”
Section: Discussionmentioning
confidence: 57%
“…In addition, a series of mitochondrial proteins, such as mitochondrial carrier proteins, altered inheritance of mitochondrial proteins 24 and some genes related to cytochrome proved to have connections with mitochondria, as identified by mass spectrometry of MoHse1, which revealed that its absence may affect mitochondrial function. Research on CmAim24 exhibited significantly reduced conidial production and germination as well as reduced sclerotial mycoparasitic ability (Yang et al ., 2020). Overexpression of the mitochondrial carrier protein Ant1 will cause EGR1, eEF1a and ubiquitin C to be upregulated, which are known to promote autophagy, protein targeting to aggresomes and the processing of protein aggregates, respectively (Liu et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Among them, several previously reported signalling pathways, including those associated with mitochondrial structure and function, ROS accumulation and peroxisomes, are upstream of the intrinsic apoptotic pathway (Albert & Sellem, 2002; Jiang & Wang, 2004; Osiewacz & Borghouts, 2000; Scheckhuber et al., 2007; Sharon et al., 2009; Smith et al., 2010; Tanaka et al., 2019). Certain genes, such as CmNox1 , CmPEX6 , CmAim24 and PIF1 , play essential roles in ROS generation, oxidant production, mitochondrial morphology regulation and maintaining mitochondrial stability (Rogers et al., 2008; Wei et al., 2013, 2016; Yang et al., 2020), indicating their critical involvement in regulating conidiation and mycoparasitism through the mitochondrion‐dependent apoptosis pathway.…”
Section: Discussionmentioning
confidence: 99%